A gestão em rede em territórios de vulnerabilidade social: círculos de diálogos com docentes gestoras - Leal, Luciéli da Conceição (2023)
This study is linked to the Postgraduate Program in Public Policies and Educational Management, Professional Master's degree, within the LP2 Pedagogical Management and Educational Contexts line. Its research object is network school management in territories of social vulnerability. Network Management is understood as the process established between school managements within the same territory, having shared values and objectives based on collaborative and collective construction regarding the democratic management of public schools. It constitutes a possibility of weaving connections between school managements, characterizing itself as an emerging context capable of driving confrontations related to school management. Thus, the general objective was defined as recognizing the implications of collective and collaborative network management for strengthening the management processes of schools in territories of social vulnerability. The specific objectives are: to understand the trajectories of teacher managers in schools in territories of social vulnerability and their specificities of managerial teaching; to comprehend the challenges of school management in territories of social vulnerability in the northern region of the Municipality of Santa Maria; to identify the possibilities of network work among school managements in the northern region to qualify the model of the annual School Pedagogical Action Plan of the Municipal Education Network (RME) of Santa Maria. The main concepts are supported by authors such as Freire (2022), Morin (2021), Powaczuk (2020, 2021), Lück (2013), Paro (2016), Pranis (2010), among others. The research is characterized by a qualitative narrative sociocultural approach, developed from circles of peace-building in the model of dialogue circles with teacher managers from 6 municipal schools that make up the territory of the northern region of the Municipality of Santa Maria/RS. The study showed that the fabric of collective and collaborative network management requires understanding about the ongoing trajectories of managerial teaching, which refers to the demands of the role and the produced meanings; that the perspective of collective and collaborative network management among schools is a key element to strengthen the management processes of schools in shared territories, among which those of social vulnerability stand out. The opportunity for systematized and planned meetings allowed establishing connections between experiences, needs, and network possibilities, indicating possibilities for strengthening school management in territories of social vulnerability in the northern region from a multiplicity of connection points. Connections that proved necessary for weaving a collective and strong network, in the approaches between schools and managements. Thus, as an educational product, a proposal for shared actions among schools was developed, which will be included in the annual School Pedagogical Action Plan providing space/time for training for managers through dialogue circles and possibilities for strategic network actions among schools. Such a product, from an expanded perspective, will be directed to the maintaining authority with the proposal for restructuring the current document of the annual School Pedagogical Action Plan, foreseeing the Network Management item and strategies to be developed among schools.